Hermeneutika Tafsir Al-Qur’an Tawaran Muhammad Al-Ghazali dalam Pemaknaan Al-Qur’an - Otong Suhendar (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2019)
This paper explains two things. Firts, understanding about hermeneutics as a Qur’anic textual commentary method. Second, the usage of heurmenetics method by Muhammad al-Ghazali. Descriptive alalysis and library research method used in this paper. It can not be denied that hermeneutics often used by contemporary Islamic shcolars for it contains novelty in order that the Qur’an can easly be understand and has a response to the times. In his commentary, Muhammad al-Ghazali emphasizes messege understanding of Qur’anic verses in accordance to the time of sending down on one side and understanding of asbab al-nuzul as a background that can be attracted to recent reality. Al-Ghazali also empasizes original Qur’anic word and sentence understanding and the growth of social humanities science utilization. Both are al-Ghazali typical tought.